Pengaruh Bermain Wayang Tema Terhadap Kemampuan Berbicara Pada Anak Usia 5-6 Tahun Di RA Masithoh Bantar - Suratiyah, Suratiyah; Fauzi, Fauzi (Jurnal Anak Usia Dini Holistik Integratif (AUDHI), 2024)
This research aims to determine the effect of playing shadow puppets on the speaking abilities of young children at RA Masithoh Bantar. The type of research used is a quantitative method with a pre-experimental design. Data collection methods used were observation, questionnaires, interviews, and documentary methods. Experienced teachers made sure the tools we used to collect information were accurate and reliable. Data analysis was carried out using normality tests and hypothesis tests, and managing this research data was assisted using SPSS 16.0. The research results obtained are: 1). The average score after playing the theme wayang is 45.13, which is higher than the average score before playing the theme wayang, namely 31.87; 2) The significance value of the nuji t-test is 0.000 because (p <0.05), then Ho is rejected and Ha is accepted, which means there is a difference in the score results before and after playing the puppet theme; 3). The correlation value of the pretest and posttest results of 0.783 is relatively high because it is almost close to 1. The significance value is 0.000, meaning that the pretest and posttest results are very significantly correlated. In other words, it means that playing themed puppets has an influence on the speaking ability of early childhood class B di RA Masithoh Bantar with a percentage increase of 41.60%.